PENGARUH KEPEMIMPINAN DAN KNOWLEDGE MANAGEMENT TERHADAP KINERJA USAHA MIKRO, KECIL DAN MENENGAH KABUPATEN KARAWANG - E Andi Ali Said; Dede Jajang Suyaman2; Nunung Nurhasanah; Sony Hersona GW (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research was conducted on MSMEs in Karawang Regency in the food business sector. The type of research is quantitative with associative techniques. The sample used was 100 MSMEs with sample determination using the Simple Random Sampling technique. The data analysis technique used is multiple linear regression analysis technique. The research results show that leadership and knowledge management partially influence the performance of MSMEs while simultaneously showing that the contribution of both variables is 14.1% and has an effect on increasing the performance of MSMEs in the food sector in Karawang Regency. This means that improving the performance of MSMEs is influenced by these two variables, even though the contribution is low, they play a role in improving the performance of MSMEs.